Chemical composition, antioxidant potential and antimicrobial activities of Ixora scheffleri subspecies keniensis essential oil - Peter K. Njenga; Samuel M. Mugo (AOSIS, 2020)
Background: Essential oil (EO) obtained from Ixora scheffleri subspecies (subsp.) keniensis has valuable biological properties and can play a possible therapeutic role because of its antimicrobial and antioxidant nature. Aim: In this article, the chemical constituents, antimicrobial activity and antioxidant capacity of the EO obtained from Ixora scheffleri subsp. keniensis were determined using standard procedures. Setting: Plant material collection, essential oils extractions and antimicrobial assays were performed at Jomo Kenyatta University of Agriculture and Technology (JKUAT), Department of Botany Laboratories. Gas Chromatography Mass Spectrophotometry (GC/MS) analysis was carried out at the Physical Science Laboratory, MacEwan University, Canada. Methods: The chemical constituents were determined using GC/MS. The total phenol content was evaluated using the Folin-Ciocalteu procedure. The antioxidant activity was determined using 2,2-diphenyl-1- picrylhydrazyl (DPPH) and β-carotene linoleic acid assays. The antimicrobial assay was performed using the disc diffusion method. Results: The total phenol content of the EO was estimated to be 91.6 µg/mg ± 0.5 µg/mg. The antioxidant activity of EO obtained from Ixora relative to ascorbic acid was found to be 52% using the β-carotene linoleic acid assay. The DPPH scavenging activity of 30 µg/mL EO obtained from Ixora and 30 µg/mL ascorbic acid was 81.65% and 97.0%, respectively. The EO was found to have significant susceptibility against Escherichia coli, and intermediate susceptibility against Candida albicans. However, Staphylococcus aureus, Bacillus subtilis and Pseudomonas aeruginosa showed complete resistance. Conclusion: The in vitro chemical compositional analysis of EO obtained from Ixora scheffleri subsp. keniensis confirms the presence of phenolic compounds attesting to the antioxidant properties and antimicrobial properties.